2013
DOI: 10.1002/adma.201304098
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Microrobotic Platform for On‐Demand, Targeted Therapeutic Interventions

Abstract: The presented microrobotic platform combines together the advantages of self-folding NIR light sensitive polymer bilayers, magnetic alginate microbeads, and a 3D manipulation system, to propose a solution for targeted, on-demand drug and cell delivery. First feasibility studies are presented together with the potential of the full design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
270
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(282 citation statements)
references
References 61 publications
1
270
2
Order By: Relevance
“…We utilize similarly designed grippers to realize closed-loop control and obtain levels of precision and reliability that are not achievable in open-loop. Closed-loop control of hydrogel grippers have also been reported by Fusco et al [14], [15]. The main differences between [14], [15] and our study are: a) The previously reported grippers in [14], [15] were not magnetic themselves and so magnetic motion control was only possible when they gripped onto a magnetic object.…”
Section: A Related Workcontrasting
confidence: 46%
See 1 more Smart Citation
“…We utilize similarly designed grippers to realize closed-loop control and obtain levels of precision and reliability that are not achievable in open-loop. Closed-loop control of hydrogel grippers have also been reported by Fusco et al [14], [15]. The main differences between [14], [15] and our study are: a) The previously reported grippers in [14], [15] were not magnetic themselves and so magnetic motion control was only possible when they gripped onto a magnetic object.…”
Section: A Related Workcontrasting
confidence: 46%
“…Closed-loop control of hydrogel grippers have also been reported by Fusco et al [14], [15]. The main differences between [14], [15] and our study are: a) The previously reported grippers in [14], [15] were not magnetic themselves and so magnetic motion control was only possible when they gripped onto a magnetic object. (b) Previously near-IR radiation was used to heat the grippers whereas here we use a Peltier element, and (c) the numerical results and analysis of the closed-loop motion control and pickand-place tasks were not reported so the accuracy and of previously reported tasks remains unclear.…”
Section: A Related Workcontrasting
confidence: 45%
“…At the microscale, soft active materials have enriched microrobots with additional functionalities, e.g. ondemand drug release 30,31 , and LCEs have recently actuated a walking microrobot 32 .…”
Section: Introductionmentioning
confidence: 99%
“…At the microscale, soft active materials have enriched microrobots with additional functionalities, e.g. ondemand drug release 30,31 , and LCEs have recently actuated a walking microrobot 32 .Nevertheless, despite their soft bodies these microrobots have each a unique function, predefined by its form, and few DOFs.Here we present the use of structured light to power and control intra-body shape changes in microrobots. The technique enables fully-artificial, self-propelled microswimmers.…”
mentioning
confidence: 99%
“…For locomotion, microrobot power must be transduced into motion [69]. The actuation method must be chosen based on the operational environment (e.g., blood vessels, soft tissues, cavities, and etc.)…”
Section: Actuation and Controlmentioning
confidence: 99%